Characteristic and Surge Impedance Variation Impact on Transmission Line Performance - Muhyaddin J. H. Rawa (Institute of Advanced Engineering and Science, 2018)
Modeling of power systems is essential to perform various network analyses. Voltage regulation, line losses and transmission line efficiency are greatly affected by transmission line parameters. Hence, accurate modeling of transmission line is required. The aim of this paper is to study the impact of characteristic and surge impedances on voltage profile, voltage regulation and transmission line efficiency.